Ageing, aerobic capacity and insulin sensitivity in masters athletes: endurance and speed-power training benefits - Kusy, Krzysztof; Zieliński, Jacek (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Aerobic capacity, insulin sensitivity and other cardiovascular and metabolic characteristics determine our health and quality of life. Masters athletes may be regarded as a model population for the assessment of the age-related functional decline, due to their chronic physical activity and lack of factors associated with secondary ageing. So far, ageing studies have concentrated on endurance-trained athletes. Masters speed-power athletes have not been the focus of attention as regards successful ageing and health. This review presents health outcomes in speed-power athletes (SP)with long-standing competitive sport participation compared to endurance-trained athletes (ER) and untrained subjects (UT).Results. SP show a lower level of maximal and submaximal aerobic capacity than ER, but significantly higher than UT. Insulin sensitivity and β-cell function in SP are relatively stable across a wide age range (20−90 years) and comparable to these parameters in ER, whereas in UT glucose metabolism visibly deteriorates with age. Some effects of speed-power training are more beneficial than endurance training. These are a slower rate of decline in aerobic capacity and some cardiorespiratory parameters, especially after the age of 50, and a more stable β-cell function. Moreover, masters printers have better neuromuscular function, higher bone mineral density and lean body/muscle mass than endurance athletes. At the same time, SP’s lipid profile is normal and the risk connected with overload of ligaments and tendons seems to be similar to that in ER. Long-term intensive endurance training, in turn, may induce deleterious changes in the cardiovascular system and increase the risk of some types of heart arrhythmias. Moreover, speed-power training may facilitate the adherence to physical activity. Conclusions. The “speed-power model” of lifelong physical activity should be considered an alternative proposal to support recommended levels of aerobic capacity, insulin sensitivity and other health characteristics with ageing
Keywords: maximal oxygen uptake; gas exchange threshold; homeostatic model assessment; β-cell function; physical activity; successful ageing